Building Community and Collaboration Applications for MMOGs - George Adam; Christos Bouras; Vaggelis Kapoulas; Andreas Papazois (International Journal of Computer Games Technology)
Supporting collaborative activities among the online players are one of the major challenges in the area of Massively Multiplayer Online Games (MMOG), since they increase the richness of gaming experience and create more engaged communities. To this direction, our study has focused on the provision of services supporting and enhancing the players' in-game community and collaboration activities. We have designed and implemented innovative tools exploiting a game adaptation technology, namely, the In-game Graphical Insertion Technology (IGIT), which permits the addition of web-based applications without any need from the game developers to modify the game at all, nor from the game players to change their game installation. The developed tools follow a design adapted to the MMOG players' needs and are based on the latest advances on Web 2.0 technology. Their provision is performed through the core element of our system, which is the so-called Community Network Game (CNG) Server. One of the important features provided by the implemented system's underlying framework is the utilization of enhanced Peer-to-Peer (P2P) technology for the distribution of user-generated live video streams. In this paper, we focus on the architecture of the CNG Server as well as on the design and implementation of the online community and collaboration tools.